Curriculum development for student agency on sustainability issues: An exploratory study - Rap, Shelley; Blonder, Ron; Sindiani-Bsoul, Ayshi; Rosenfeld, Sherman (Frontiers in Education, 2022)
Despite unprecedented global challenges to the environment, research show that many young people are pessimistic about their ability to address these challenges. This paper explores one approach designed to guide middle-school teachers and their students to develop and practice agency about sustainability issues: via a curriculum that challenges students to solve problems by analyzing real-world data and developing scientific arguments, as a basis for engaging in activism. The paper begins with an overview of the United Nation’s Agenda 2030, its Sustainable Development Goals (SDGs), the related aims of Education for Sustainable Development (ESD), and a review of what is meant by student agency. Next, the goals and design features of a curricular initiative, “Speak to Me in Numbers,” are presented with a brief presentation of two units, each based on a different SDG. The paper’s research questions are (1) How were the design features of the curriculum perceived by the teachers? and (2) What were the preliminary outcomes of the curriculum in terms of student and teacher argumentation skills and student activism? To address these questions, we present an exploratory study: observations and comments from in-service teachers and participating students regarding preliminary outcomes of the curriculum that might be related to the development of student agency. In our concluding discussion, based on these findings and relevant literature, we suggest that a promising pedagogy to strengthen student agency on sustainability issues is a data-driven pedagogy that focuses on the development of scientific argumentation, mathematical thinking and activism.